Model Kebaya Encim Ditinjau dari Perspektif Pendidikan Islam dan Implemntasinya Sebagai Busana Muslimah Pendidikan Busana Muslim - Lesmanasari, Aprivianda Endah; Saidah Yusrie, Chaira H; Riyanto, Riyanto (Transformasi Manageria: Journal of Islamic Education Management, 2024)
Kebaya is one of the traditional clothes in Indonesia. Kebaya is a top garment that has the characteristic of being open at the front and has long sleeves. Usually worn with a long cloth. One type of kebaya is kebaya encim. Kebaya encim is a traditional Betawi clothing that is synonymous with elements of Chinese culture. Kebaya encim is a blend of Betawi, Chinese and Malay cultures. At first, kebaya was worn by the nobles. Along with the development of the times and technology, kebaya can be used by all walks of life by leaving the old rules. Education is a process of changing attitudes towards a group of people in making efforts to grow up through learning and training efforts. Islamic education is an effort in the form of guidance and nurturing for students so that later after their education is completed, they can understand and practice the teachings of Islam and make it a view of life. Islamic education is education that is carried out based on Islamic teachings. Muslim women's clothing is clothing that is in accordance with Islamic religious law. Kebaya can be used as Muslim clothing if the kebaya model is adjusted to the provisions of Islamic law. The criteria for Muslim women's clothing are to cover the aurat, not transparent and not show the curves of the body. To fulfill the elements of Muslim women's clothing, it is necessary to modify the encim kebaya according to Islamic sharia by lengthening the length of the kebaya, lengthening the arms and by making the size larger than the body size so as not to form curves.